Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 8 - Section 8.3 - Solving Equations by Using Quadratic Methods - Exercise Set - Page 501: 20



Work Step by Step

We can write the given equation as: $(x^{1/3})^2+2x^{1/3} +1=0$ Let $u=x^{1.3}$ Then $u^2= (x^{1/3})^2$ Rewrite the given equation using the variable $u$ to obtain: $u^2+2u+1=0$ Factor the trinomial to obtain: $(u+1)(u+1)=0$ Use the Zero-Factor Property by equating each unique factor to zero. then solve: $u+1 = 0 \\u=-1$ Since $u=x^{1/3}$, then $u= -1 \\x^{1/3}=-1 \\(x^{1/3})^3=(-1)^3 \\x=-1$ Thus, the solution is $x=-1$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.